Desempenho agronômico e qualidade das sementes de diferentesgenótipos de girassol, no norte de Minas Gerais - Danubia Aparecida Costa Nobre (2012)
The sunflower (Helianthus annus L.) is one of the four cultures of biggerproduction of edible oil in the world. It is a food complement for animals,increment in beekeeping and presents potential for biodiesel production. It stands out for its adaptation to different edafoclimatic conditions. The present research was developed with the objective to determine the agronomic performance and seed quality of different sunflower genotypes in the North of Minas Gerais. The study was conducted at the Experimental Farms of the Agricultural Research Company of Minas Gerais (Epamig) in the municipalities of Jaíba, District of Mocambinho and Nova Porteirinha. The evaluations of agronomic performance were: initial flowering, plant height, stem diameter, leaf number, chapter length, final stand, grain yield and oil content, for seed quality: water content, mass of 1000 seeds , biometrics seed (length, width and thickness), germination test, first germination count, rate of speed of germination, tetrazolium test and sanity test of the seed. The data collected were subjected to analysis of variance and the Scott-Knott test at 5% probability. There was variation in all parameters evaluated in agronomic behavior of genotypes, which presented good performance whengrown in the north of Minas Gerais. The genotypes evaluated presented early cycle, except SYN 039A, with a medium cycle. There was a reduction in the majority of the evaluated variables, with the reduction of the culture cycle. The seed mass and biometry are characteristics related to genotypes and their adaptation to local of production, not interfering in the quality of seeds. For the genotypes evaluated in the north of Minas Gerais, only the CNZ CIRO and HLA 11-26 presented low germination. The Helium 358, CF 101 and M 734, collected in Mocambinho and the genotypes SYN 034A and SY 3840, to Nova Porteirinha, presented low vigor and viability by the tetrazolium test. The detected fungi in the seeds collected in Mocambinho had influence on vigor and germination of the genotypes CNZ CIRO and HLA11-26.